Relics habitat of mangrove vegetation in south coast of Java - AHMAD DWI SETYAWAN; ARI SUSILOWATI; WIRYANTO WIRYANTO (Biodiversitas Journal of Biological Diversity, 2002)
Mangrove vegetation is one of the most richness ecosystems in tropical forest. It has high value economically and ecologically. Mangrove product can be used directly as timber, firewood, charcoal, tannin, dyes, food, medicine, raw material of industries, etc. It also can be used indirectly as fisheries, wastes processing, seashore protection, ecoturisms, educations, etc. In the past time, river estuaries in south coast of Java was mangrove habitat. However, anthropogenic activities had been reduced mangrove vegetation into relix habitat. The aim of the research was to know (1) sites of mangrove vegetation in river estuaries in south coast of Java, (2) diversity of mangrove vegetation, (3) density of Sonneratia alba J.E. Smith, and (4) physical and chemical properties of these sites. The research was conducted in March-April 2002, at 20 river estuaries from Pacitan until Cilacap, south coast of Java. The results indicated that mangrove remnant could be met in 10 river estuaries, namely Grindulu, Teleng, Bogowonto, Cakrayasan, Lukulo, Cincingguling, Ijo, Bengawan, Serayu, and Jeruk Legi-Donan. There were 29 mangrove species in estuaries, consist of major components (9 sp.), minor components (2 sp.), and mangrove associated (18 sp.). The density of Sonneratia alba J.E. Smith varied from 0 till > 250 individual per hectare. The soil sediment could be grouped into sand, silt, and clay, where silt and clay could support mangrove growth finely. The average of environmental parameters as follows: temperature of water and sediment respectively were 32.0oC and 31.4oC, pH of water and sediment respectively were 7.29 and 6.96, total dissolved solid of water was ~ 2000 ppm, dissolved oxygen of water was 9.29 ppm, and water salinity was 16 ppt.Â© 2002 Jurusan Biologi FMIPA UNS SurakartaKey words: mangrove remnant, Sonneratia alba, diversity, density